2016
DOI: 10.1021/acs.orglett.6b02045
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Enantioselective Three-Component Synthesis of α-Arylglycines

Abstract: A general Pd-catalyzed, enantioselective three-component synthesis of α-arylglycines starting from sulfonamides, glyoxylic acid derivatives, and boronic acids was developed. This operationally straightforward procedure enables the preparation of a wide variety of α-arylglycines in high yields and excellent levels of enantioselectivity from a simple set of readily available starting materials. Incorporation of Pbf-amides gives a racemization-free access to N-unprotected α-arylglycines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 81 publications
0
26
0
1
Order By: Relevance
“…Subsequent amine protection using 2,2,4,6,7-pentamethyl-2,3-dihydrobenzofuran-5-sulfonyl enabled the racemization-free removal of the sulfonyl group to give the corresponding free amines. 74 Previously, the same research group reported the enantioselective synthesis of α-arylamines using a palladium-catalyzed PR, using the chiral tetrahydrobioxazole ligand 26 , of aldehydes, sulfonamides, and arylboronic acids. 63 In addition to the previously mentioned examples of catalysis, ultrasound irradiation has also been used to promote the PR of glyoxylic acids in the synthesis of α-arylglycines.…”
Section: Three-component Petasis Reactionsmentioning
confidence: 99%
“…Subsequent amine protection using 2,2,4,6,7-pentamethyl-2,3-dihydrobenzofuran-5-sulfonyl enabled the racemization-free removal of the sulfonyl group to give the corresponding free amines. 74 Previously, the same research group reported the enantioselective synthesis of α-arylamines using a palladium-catalyzed PR, using the chiral tetrahydrobioxazole ligand 26 , of aldehydes, sulfonamides, and arylboronic acids. 63 In addition to the previously mentioned examples of catalysis, ultrasound irradiation has also been used to promote the PR of glyoxylic acids in the synthesis of α-arylglycines.…”
Section: Three-component Petasis Reactionsmentioning
confidence: 99%
“…In the course of our work on the palladium-catalyzed, stereoselective three-component synthesis of α-substituted amides, [6][7][8][9] we became aware of a gap in the substrate scope.…”
mentioning
confidence: 99%
“…Manolikakes and co‐workers published a series of papers relating to Pd‐catalyzed multicomponent reactions between an arylboronic acid 86 , a sulfonamide 2o , and an aldehyde 3b . After initial studies on the racemic version, they reported an enantioselective version with use of ( S , S )‐ i PrBOX as a ligand (Scheme ).…”
Section: Sp2 Nucleophilesmentioning
confidence: 99%